A Peep into the History and Experiences of the Cooperative Movement in Zambia - Mundia, Mukwalikuli; Wamundila, Sitali; Siakalima, Daniel; Nkonde, Chewe; Simui, Francis (Advances in Social Sciences Research Journal, 2021)
This study is a reflection on the history and experiences of cooperative movement in Zambia in three stages (the colonial era, from 1914 to 1963, the post-colonial era from 1964 to 1990 and the cooperative movement in the liberalized economy in Zambia, from 1991 to present). The study used secondary data from various studies. The thrust of this study explored the history and experiences of cooperative movement in Zambia and how the economic and political changes affected the cooperative movement in Zambia. This information is very critical, especially to those who would want to enhance and harness the cooperative movement in Zambia. Emergent from this study is the continued political and econmic influence on cooperatives. Cooperatives were noted to be struggling to cope with the stiff competition, which was due to the liberalization of the economy in the country. The current poor performance by cooperatives was attributed to the failure to swiftly change from the 1964 to 1991 era, where cooperatives were operating as channels for distrusting government resources in a closed economy. Thus, it is recommended among others that, Government should stop the issue of imposing projects on the cooperative communities, business ideas should come from the cooperatives members themselves as a way of entrenching business ownership. In addition, cooperatives societies should start being innovative in order for them to be able stand the stiff competition which is due to the liberalization of the economy.